Kecepatan Penyesuaian Leverage : Bukti Empiris Perusahaan Pertambangan di Indonesia - Garnis Irawanti; Koko Safitri (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
This study aims to examine the speed of target adjustment and the company's leverage. Mining companies listed on the Indonesia Stock Exchange for the period 2015 to 2020 are the objects of this research, especially in terms of examining the factors that affect the speed of adjustment to the target leverage. This study uses a sample of 34 mining companies in conducting observations. This study uses a dynamic approach that takes into account the possible deviations between the actual leverage ratio and the company's targeted leverage ratio. The results of the study show that 1) the speed of leverage adjustment made by mining companies in Indonesia is still influenced by adjustments to the costs borne by the company, the adjustment time, and the process of making adjustments, even though leverage adjustment is very necessary in achieving company profitability. 2) Profitability has a significant effect on speed adjustment. This is because profitability is the main source of funding for the company. So it can be said that leverage adjustment requires an increase in profitability. 3) Firm size has a negative effect on the speed of adjustment. Consideration of the costs that will be faced by the company if making adjustments, is a reason for companies not to immediately make adjustments. 4) Company growth has a positive effect on speed adjustment. Companies with high growth, it is easier to change the composition of their capital structure by changing the composition of new capital 5) Distance has a negative effect on the speed of adjustment. The further the deviation (distance) between the target leverage and the actual leverage, the slower the adjustment made by the company.